MyUiTMPerak App / Azlizan Adila Mohamad ... [et al.] - Mohamad, Azlizan Adila; Ahmad Pugi, Noorsazwan; Nasron, Nursyahani; Mohamad, Azlinda (2020)
Life as a freshman at the university can be an anxious and scary moment for every student because they are not familiar to the new environment. Even though the existence of smartphones equipped with GPS technology can help them cope with this situation, existing mapping service applications such as Google Maps and Waze do not provide comprehensive information on the campus and its surrounding environment. Therefore, MyUiTMPerak app is developed to assist students and visitors to (1) obtain information on campus; (2) identify locations on campus; and (3) navigate to the destination on campus. MyUiTMPerak is an interactive mobile mapping application of the UiTM Perak Branch campus that can be easily installed on every student and visitor smartphone. By using the AppSheet platform, the location and information of every place in UiTM Perak Branch campus are stored to enable this app to show the area within the campus. This mobile app can facilitate new students and visitors to go to the desired place in the campus of UiTM Perak Branch.